(untitled) (World Bulletin of Public Health, 2022)
This experiment was conducted to find out the therapeutic effect of genistein as an antioxidant and anti-inflammatory in reducing the negative effects caused by morphine on the level of testosterone hormone and testicular tissue. 48 male laboratory mice divided into four groups were used. Each group included 12 mice, and the control group injected 0.1 M of normal saline. The morphine group was injected at a concentration of 20 mg/kg, and the genistein group was injected at a concentration of 25 mg/kg. Finally the morphine and genistein group that was injected with morphine at a concentration of 20 mg/kg for 15 days, and then injected with genistein at a concentration of 25 mg/kg for 15 days; Mice were injected once daily subperitoneally and divided into three periods (five, ten and fifteen days after injection). The results of the statistical examination showed a significant decrease in the morphine group in a period of 5 days, the morphine and Genistein group and the Genistein morphine group after 10 days, and the results showed a significant decrease at the probability level (P <0.05)) for the second treatment compared with other treatments during the fifteen days of injection .The results of the histological examination showed the presence of some histopathological changes compared to the control group, where the results of the histological examination of the testicles five days after the injection showed the presence of necrosis in the seminiferous tubules, the decomposition of the primary sperm, and after ten days of the injection there was a lack of spermatogenesis with no development in animal production. The primary spermatozoa and the occurrence of necrosis in the seminiferous tubules and hyperpigmentation of the sperm cells, while the tests showed fifteen days after the injection the presence of severe necrosis of the spermatogenetic tissue and the complete loss of sperm production with the loss of development of the primary spermogenic cells >